2018
DOI: 10.1111/and.12967
|View full text |Cite
|
Sign up to set email alerts
|

Health-related physical fitness and quality of life in men with congenital hypogonadotropic hypogonadism

Abstract: Congenital hypogonadotropic hypogonadism is a rare disorder characterised by impaired testosterone secretion since birth, and represents a valuable model for studying the effects of testosterone replacement therapy (TRT) in humans. This cross-sectional study aimed to investigate all health-related physical fitness (HRPF) components and quality of life in a series of eight men with hypogonadotropic hypogonadism under regular TRT. The study group was compared to a control group of 16 healthy subjects paired for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Surprisingly, we found that the untreated patients experienced a comparable level of overall HRQoL, SS and depressive symptoms as the hormonally treated IHH subjects. Our results are contrary to those of Mileski et al, who observed that QoL is similar in hypogonadism under regular TRT compared to healthy male volunteers [42]. The fact that a relatively small group of untreated patients completed the given questionnaire could have influenced such a comparison in our study.…”
Section: Hormonal Treatment Satisfaction and Adherencecontrasting
confidence: 99%
“…Surprisingly, we found that the untreated patients experienced a comparable level of overall HRQoL, SS and depressive symptoms as the hormonally treated IHH subjects. Our results are contrary to those of Mileski et al, who observed that QoL is similar in hypogonadism under regular TRT compared to healthy male volunteers [42]. The fact that a relatively small group of untreated patients completed the given questionnaire could have influenced such a comparison in our study.…”
Section: Hormonal Treatment Satisfaction and Adherencecontrasting
confidence: 99%
“…Previous studies comparing results from the PFT to laboratory measurements of VO2max as a reference method have demonstrated that the PFT is a valid (accurate) and reliable (consistent) method for assessing aerobic capacity in human subjects [Vainamo et al, 1998;Vainamo et al, 1996;Polar, 2019a]. Further, the PFT is commonly used in the exercise physiology literature for the assessment of aerobic capacity [Mileski et al, 2018;Brum et al, 2013;Tumiati et al, 2008;Borodulin et al, 2006;Borodulin et al, 2005;Borodulin et al, 2004].…”
Section: Polar Oh1 Optical Heart Rate Sensormentioning
confidence: 99%
“…Since traditional exercise programs train muscles and not movements, traditional exercise programs offer little in terms of functional performance benefits and can even lead to functional performance deficits, pain, and injury [Clark, Lucett, Kirkendall, 2010]. Given the growing interest in functional training programs over traditional exercise programs, fitness clubs have increasingly incorporated more functional training tools (TRX suspension systems, ViPRs, medicine balls, battle ropes, kettlebells, and fitness playground setups), functional training classes (boxing, kickboxing, and obstacle courses), and more open space into their training environments to facilitate functional training among club members [Rubin, 2013;McCall, 2019]. In fact, between 2013 and 2018, nearly 4,000 boxing gyms opened in the United States and the boxing fitness industry made a total of $1.2 billion [Landsverk, 2019].…”
mentioning
confidence: 99%
“…Testosterone (1, androst-4-en-17β-ol-3-one or 17β-hydroxyandrost-4-en-3-one), the major male sex hormone naturally secreted by Leydig cells in the testes, is an organic molecule important not only from a physiological point of view [as it is essential for male sexual differentiation, growth and function of the male genital tract, masculinized secondary sexual characteristics, sexual potency, production of spermatozoa (spermatogenesis) and male fertility], but also from the perspective of medicinal chemistry and drug design. 1 Therefore, testosterone provides a key starting material for various active pharmaceutical ingredients (API) of many registered drugs, which are most often used to treat a variety of endocrine disorders, such as male hypogonadism (hypoandrogenism) [2][3][4] and hypoactive sexual desire disorder in women (HSDD). [5][6][7][8] While testosterone constitutes a prominent example of an anabolic-androgenic steroid (AAS) substance, it is also utilized for distinct androgen-requiring therapies along with male-hormone replacement therapy (M-HRT), [9][10][11] female androgen deficiency syndrome (FAIS) therapy, [12][13][14][15] and the masculinizing hormone therapy.…”
Section: Introductionmentioning
confidence: 99%